Effects of kiwi fruit (Actinidia chinensis) polysaccharides on metabolites and gut microbiota of acrylamide-induced mice - Chen, Mengyin; Chen, Xuefeng; Wang, Ketang; Cai, Luyang; Liu, Nannan; Zhou, Duan; Jia, Wei; Gong, Pin; Liu, Ning; Sun, Yujiao (Frontiers in Nutrition, 2023)
Kiwifruit (Actinidia chinensis) has rich nutritious and medicinal properties. It is widely consumed worldwide for the intervention of metabolism disorders, however, the underlying mechanism remains unclear. Acrylamide, a well-known toxic ingredient, mainly forms in high-temperature processed carbohydrate-rich food and causes disorders of gut microbiota and systemic metabolism. This study explored the protective effects and underlying mechanisms of kiwifruit polysaccharides against acrylamide-induced disorders of gut microbiota and systemic metabolism in mice. The results showed that kiwifruit polysaccharides remarkably alleviated acrylamide-induced toxicity in mice by improving their body features, histopathologic morphology of the liver, and decreased activities of liver function enzymes. Furthermore, the treatment restored the healthy gut microbiota of mice by improving the microbial diversity and abundance of beneficial bacteria such as Lactobacillus. Metabolomics analysis revealed the positive effects of kiwifruit polysaccharides mainly occurred through amino and bile acid-related metabolism pathways including nicotinate and nicotinamide metabolism, primary bile acid biosynthesis, and alanine, aspartate and glutamate metabolism. Additionally, correlation analysis indicated that Lactobacillus exhibited a highly significant correlation with critical metabolites of bile acid metabolism. Concisely, kiwifruit polysaccharides may protect against acrylamide-induced toxicity by regulating gut microbiota and metabolism.